Diabetes and travel insurance costs: let's talk about remission. (13th February 2019) - Angelopoulou, Kleopatra; Leslie, Wilma; McCombie, Louise; Lean, Mike; Hankey, Catherine
Abstract : The growing global prevalence of type 2 diabetes mellitus places enormous burden on health services and affected individuals. As with other medical diagnoses, the presence of type 2 diabetes will impact on premiums for things such as travel insurance. Interventions which result in remission of what was previously viewed as a chronic progressive disease are attracting interest from health service providers and people with the disease. We investigated the influence of type 2 diabetes status on travel insurance through obtaining quotes for a set number of scenarios from a variety of providers. It was found that at this point there is inconsistency across travel insurance providers in terms of the impact of diabetes status on premiums paid with no specific recommendations for people who meet the criteria for remission coding. People with type 2 diabetes, including those who have achieved remission, should be advised to seek quotes from various providers in order to get the most advantageous cover for premiums paid. Copyright © 2019 John Wiley & Sons.